Simulation Research on Leakage of Vehicle CO2 Air Conditioning System - Zong Shuo; Yin Xiang; Huang Longfei; Song Yulong; Cao Feng (Zhileng xuebao)
As a safe, efficient, and environmentally friendly natural working fluid, CO2 is the primary choice for future automotive air conditioners. To consider the comfort and safety problem of an excessive CO2 volumetric concentration in the passenger cabin caused by refrigerant leakage, the 3D simulation software STAR-CCM+ was used to build a CO2 refrigerant leakage model in the passenger compartment. Simulations and analyses of the dynamic changes in CO2 volumetric fraction in the passenger compartment facial measurement points for two different leakage rates and leakage orifice diameters were performed. At a high CO2 leakage rate of 50 g/s, the CO2 volumetric fraction on the face can reach more than 9% when the leakage is completed. The air supply mode must be switched to provide fresh air and reduce the CO2 volumetric fraction in the passenger cabin. At a low CO2 leakage rate of 0.1 g/s, the facial CO2 volumetric fraction does not exceed 3%, which is safe for breathing, when the leakage is completed.